The region of the Zala and Mura Rivers (Zala County) in the Late Bronze Age: Late Tumulus and Urnfield period - Száraz, Csilla (Dissertationes Archaeologicae, 2021)
Abstract of PhD thesis submitted in 2020 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Gábor V. Szabó.